Is Articaine More Potent than Mepivacaine for Use in Oral Surgery? - Giath Gazal (eJournal of Oral Maxillofacial Research)
Objectives: To investigate the potency and speed of action of 4% articaine and 2% mepivacaine for maxillary teeth extractions.